The Effect of Leverage and IFRS Convergence on Earnings Management Through Real Activities Manipulation in Asia - Wardhani, Ratna; Anggraenni, Maulia Dewi (Asian Journal of Business and Accounting, 2017)
Manuscript type: Research Paper Research aims: This study aims to examine the effect of leverage and International Financial Reporting Standards (IFRS) convergence on earnings management through real activities manipulation (RAM), and the moderation role of the IFRS convergence in the relationship between leverage and RAM. This study also explores whether the links are different based on institutional contexts such as country economic size, governance quality and IFRS adoption strategy. Design/ Methodology/ Approach: This study employs panel data and cross country analyses using 19,744 observations from six sample countries in Asia that have already adopted the IFRS, namely China, Hong Kong, Indonesia, Malaysia, the Philippines, and Sri Lanka. Research findings: This study finds that leverage has a significant negative effect on RAM, and IFRS positively affects RAM. In the period after IFRS convergence, the negative effect of leverage on RAM increases. Interestingly, this study provides mixed empirical evidence of the relationship between leverage and IFRS, and the moderation effect of IFRS on RAM across different settings of institutional contexts. This shows that institutional contexts do matter. Theoretical contributions/ Originality: This study provides empirical evidence on the effect of leverage and IFRS convergence on RAM across countries in Asia. Practitioner/ Policy implications: Regulators should make provisions to protect creditors and increase monitoring to ensure the quality of financial reporting. Research limitations/ Implications: This study covers only six countries in Asia. Future studies should cover other regions so as to enlarge the coverage of the countries that have adopted or fully converged to IFRS. This study uses several firm level control variables. Future research may include other control variables such as investor protection and types of legal system.